Houndsley and Catina and the quiet time - Howe, James 1946-; Gay, Marie-Louise (Minneapolis, Minnesota Abdo Spotlight Somerville, Massachusetts Candlewick Press, 2023)
Catina struggles with the quiet time that follows the first snow of winter, but Houndsley helps her let go of her worries and enjoy the day
Silent white -- The island -- The concert
Keywords: Cats -- Juvenile fiction; Dogs -- Juvenile fiction; Friendship -- Juvenile fiction; Quietude -- Juvenile fiction; Snow -- Juvenile fiction; Winter -- Juvenile fiction; Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Quietude -- Fiction; Snow -- Fiction; Winter -- Fiction; Cats; Dogs; Friendship; Quietude; Snow; Winter; Fiction; Juvenile works